Fetal membrane imaging: current and future perspectives—a review - Wu, Dan; Cao, Jiasong; Xu, Meiyi; Zhang, Cunling; Wei, Zhuo; Li, Wen; Chang, Ying (Frontiers in Physiology, 2024)
Fetal membrane providing mechanical support and immune protection for the growing fetus until it ruptures during parturition. The abnormalities of FM (thickening, separation, etc.) is are related to adverse perinatal outcomes such as premature delivery, fetal deformities and fetal death. As a noninvasive method, imaging methods play an important role in prenatal examination. In this paper, we comprehensively reviewed the manuscripts on fetal membrane imaging method and their potential role in predicting adverse perinatal fetal prognosis. We also discussed the prospect of artificial intelligence in fetal membrane imaging in the future.